A Study on Various Possibilities in Public Administration Education and Training in India: Exploring Public Administration Education and Training in India (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In more recent times, education and training in public administration have become very important because the public service is expected by the citizens to provide value for money spent. In developing countries, in view of the numerous developmental challenges, the call for effective public administration education and training has been extremely intensified. Consequently, there is the need to examine what governments are doing in this regard and whether initiatives being undertaken will yield the needed results.The purpose of this paper is to discuss the standards of public administration education and training in select countries in Asia. The paper presents the backdrop of public administration education and training in Asia, outlines practices of public administration in these countries and accreditation profile of these countries and offers suggestions to lift accreditation standards and practices to the global standards to the appropriate institutions.The paper presents a statistical analysis exploring public administration education in Indian universities. It highlights the main specificities of PA education in India with reference to the disciplinary character, the geographical distribution, the type and level of PA programs, etc. and aims at describing how universities are adjusting curricula in relation to public sector modernization, by comparing the main faculties (economics and management sciences, law, political sciences, sociology, engineering, sciences of communication, social sciences) of all Indian universities.